Suplementación de sales minerales en colmenas de abejas (Apis mellífera) en el recinto la Ercilia, Cantón Ventanas, año 2018. - Muñoz García, Liseth Dalmaris (2019)
Twenty beehives located in the La Ercilia village Ventanas enclosure were evaluated, where a completely random design was used with 4 treatments and 5 repetitions, each experimental unit was constituted by a hive with the purpose of evaluating the supplementation with mineral salts, for which the following variables were considered; population increase, food consumption, incidences of diseases and cost of treatments, obtaining as a result that there was no significant difference between treatments which showed us that the population in the hives remained, although statistically there was no difference in the treatment that best behavior was had the T4, on the other hand it was found that the consumption of the food supplied weekly to the hives was consumed in its entirety, this because the diets were based on sugar syrup food more used by beekeepers in times of scarcity of flowering, as we also showed that the hives used for the research were free of the most common diseases such as; European foulbrood and American foulbrood, for mite varroa destructor samples were taken which revealed that the percentage of infestation was less than 1% in each hive for which it is not necessary to apply any acaricide treatment since it is tolerated by the same bees, An economic analysis of the cost of the treatments was also carried out, where the control treatment was the lowest cost, which shows us that since there is no statistical difference between treatments, any of the supplements can be supplied in times of food shortage, resulting in The population in the hives is maintained and they are resistant to diseases that attack more frequently in times when the climate is not favorable. Key words: Supplementation, mineral salts, hives, population, diseases, consumption, costs.